Beliefs and practices of Gestant Mothers from the Vista Alegre neighborhood of Ayacucho - Saldaña Sousa, Cástor (2021)
The objective of this research is to describe and interpret the beliefs and practices of the prenatal stage of pregnant mothers who go to their prenatal checkups at the Vista Alegre Health Center in the Carmen Alto district, Ayacucho, Peru. The methodology used is qualitative and ethnographic, based on open interviews with pregnant mothers. From the perspective of health anthropology and life cycle theories, it is concluded that prenatal practices and care by pregnant mothers are influenced by beliefs of a cultural, religious and mythological nature. These factors reveal that there is a local prenatal culture compared to a westernized prenatal culture, generating difficulties in intercultural communication and, in some cases, risks to maternal and perinatal health. Key words: pregnant women, culture, anthropology of health, beliefs.